PENERAPAN MEDIA KANTONG BILANGAN PADA MATERI OPERASI HITUNG BILANGAN CACAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 4 SEKOLAH DASAR - Rahma Nida Diyana; Julianto; Ngasriati; Muzakiyah; Fitria Hidayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mathematics is considered one of the most difficult and boring subjects, leading many students to dislike it. This affects the students' low performance in mathematics. Moreover, in the fourth grade of elementary school, the topic of adding large whole numbers using carrying techniques is one of the most difficult for students to understand. Some of the reasons for this include the lack of varied teaching media used by teachers and the low motivation of students to engage in learning. The number pocket is introduced as a three-dimensional tool designed to help students perform arithmetic operations, especially addition and subtraction. Therefore, this study aims to analyze the use of number pockets in teaching large whole numbers to improve the learning outcomes of fourth-grade students in arithmetic operations, specifically addition and subtraction. The research method used is Classroom Action Research (CAR), conducted over two cycles with the subjects being 25 fourth-grade students at SDN Petemon Surabaya. Data collection techniques include written tests consisting of 15 questions. Based on the research, it can be concluded that the use of number pockets in teaching arithmetic operations on whole numbers, addition, and subtraction can improve the learning outcomes of fourth-grade students. This is indicated by an increase in student learning outcomes from 52% in the first cycle to 84% with a minimum mastery criterion (MMC) of 75 in the second cycle.